Elevational patterns of plant dispersal ability in Southern Europe. (2nd January 2023) - Di Musciano, Michele; Ricci, Lorenzo; Di Cecco, Valter; Bricca, Alessandro; Di Martino, Luciano; Frattaroli, Anna Rita
Abstract: Dispersal ability is a functional trait crucial to understand the distribution and spatial dynamics of plant species. This trait influences the abilities of a species to colonize, or thrive, in a region and thus play a central role on its distribution. We investigated the relationship between plant dispersal ability and elevational distribution (within southern Europe). Algorithms combining different plant dispersal traits, such as seed mass, release height, terminal velocity, growth form and dispersal syndrome, were used to estimate dispersal kernels of 929 vascular plant species along elevational gradient. Finally, we calculated Rao's functional diversity (FD) by analysis of standardized effect size and community mean (CM) for the dispersal distances. The main results show that species, along the elevational gradient, show different dispersal capacity. The greatest dispersal ability was detected at intermediate elevation, while a reduction in dispersal ability along with a convergence in functional diversity was observed with increasing elevation. These results can be explained by variation in environmental constraints along the elevational gradient. Thus, we conclude that short-distance dispersal is crucial in a stressed environment, while long-distance dispersal ability is advantageous to colonize new habitats where environmental constraints are weak.